Big data revolution : - Thomas, Rob (Wiley, 2015)
Big data can be a powerful tool for creating effective business solutions, but formulating and executing the right strategy requires a deep understanding of an increasingly complex subject. Big Data Revolution highlights the power, potential, and pitfalls of big data, providing the insight you need to improve business outcomes with innovation and the efficient use of technology. Companies are generating data faster than ever before, and that data can be leveraged to transform industries.